2021
DOI: 10.3390/cancers13030412
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Electron Acceptors Contributes to Redox Stress and Growth Arrest in Asparagine-Starved Sarcoma Cells

Abstract: Amino acids are integral components of cancer metabolism. The non-essential amino acid asparagine supports the growth and survival of various cancer cell types. Here, different mass spectrometry approaches were employed to identify lower aspartate levels, higher aspartate/glutamine ratios and lower tricarboxylic acid (TCA) cycle metabolite levels in asparagine-deprived sarcoma cells. Reduced nicotinamide adenine dinucleotide (NAD+)/nicotinamide adenine dinucleotide hydride (NADH) ratios were consistent with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The systemic changes observed in individual metabolite levels between +Asn and −Asn conditions in ASNS deficient cells are matched by MSEA, which shows pathway enrichments in redox, anaplerotic, and TCA cycle pathways for both LCL and fibroblasts (Supplementary Figure S2). The Asn deprivation-dependent impairments we observed in aspartate, TCA cycle intermediates, and redox balance metabolites such as glutamate, serine, and cysteine are in agreeance with metabolic dysfunction in Asn-starved sarcoma cells, as previously reported [39]. This indicates that, to some degree, ASNS deficiency in ASNSD and cancer is culminating in similar metabolic downfalls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The systemic changes observed in individual metabolite levels between +Asn and −Asn conditions in ASNS deficient cells are matched by MSEA, which shows pathway enrichments in redox, anaplerotic, and TCA cycle pathways for both LCL and fibroblasts (Supplementary Figure S2). The Asn deprivation-dependent impairments we observed in aspartate, TCA cycle intermediates, and redox balance metabolites such as glutamate, serine, and cysteine are in agreeance with metabolic dysfunction in Asn-starved sarcoma cells, as previously reported [39]. This indicates that, to some degree, ASNS deficiency in ASNSD and cancer is culminating in similar metabolic downfalls.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, recent research on ASNSD has extensively probed the molecular consequences of Asn deprivation on patient cells deficient of ASNS and found that cell survival correlates with Asn supplementation. It has been established that Asn is required to sustain protein synthesis and cell growth in both cancer and healthy cells [36][37][38][39]. There have been several metabolic analyses testing the implications of ASNS in cancer, but there is limited knowledge about the effects of Asn deprivation on the global metabolomics of the inborn error of metabolism, ASNSD.…”
Section: Discussionmentioning
confidence: 99%